2020
DOI: 10.21037/atm-20-4497
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH signalling in ovarian cancer angiogenesis

Abstract: The Notch signalling pathway is involved in the new vessel formation process by regulating tip and stalk cells, which are key cells in the sprout formation. This process is essential in both normal ovary and cancer angiogenesis and is regulated by Notch-VEGF crosstalk. Furthermore, Notch has been linked in ovary with stem cell maintenance and epithelial mesenchymal transition processes. Dysregulation of the Notch pathway is frequent in ovarian cancer (OC) and it has been associated with impaired survival and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 71 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…For example, C10orf55 has been found to be a potential biomarker to predict the relapse of acute myeloid leukemia (18). DLL4 plays a key role in tumor angiogenesis, functioning as a negative regulator of tumor angiogenesis and is upregulated in the tumor vasculature (19,20). A previous study indicated that DLL4 could be an independent prognostic factor for predicting the OS of patients with non-small cell lung cancer and was correlated with immunocyte infiltration (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, C10orf55 has been found to be a potential biomarker to predict the relapse of acute myeloid leukemia (18). DLL4 plays a key role in tumor angiogenesis, functioning as a negative regulator of tumor angiogenesis and is upregulated in the tumor vasculature (19,20). A previous study indicated that DLL4 could be an independent prognostic factor for predicting the OS of patients with non-small cell lung cancer and was correlated with immunocyte infiltration (21).…”
Section: Discussionmentioning
confidence: 99%
“…Then, navicixizumab had been further investigated in combination with paclitaxel in platinum-resistant ovarian cancer patients in a Phase 1b study (NCT03030287). By 2020, 44 patients had been included and the overall response rate (ORR) of this combination was 43% including 1 CR and 18 PR [ 118 ].…”
Section: Targeting Antigensmentioning
confidence: 99%
“…Notch signalling is detected in the early stages of pancreatic development, where it directs the recruitment of endocrine cells from their progenitor cells, but many studies also indicate that its function extends to exocrine development [42]. Notch signalling has been implicated in several human pathologies of cardiovascular origin as well as in numerous cancers [43][44][45][46].…”
Section: Notch Signallingmentioning
confidence: 99%